Dehydration-induced mechanical instabilities in active elastic spherical shells. (27th October 2021) - Curatolo, M.; Napoli, G.; Nardinocchi, P.; Turzi, S.
Abstract : Active elastic instabilities are common phenomena in the natural world, where they have the character of sudden mechanical morphings. Frequently, the driving force of the instability mechanisms has a chemo-mechanical nature, which makes the instabilities very different from the standard elastic instabilities. In this paper, we describe and study the active elastic instability occurring in a swollen spherical closed shell, confining a water-filled cavity, during a dehydration process. We set up a few numerical experiments based on a stress-diffusion model to give an insight into the phenomenon. Then, we present a study that looks at the chemo-mechanical problem and, through a few simplifying assumptions, allows us to derive a semi-analytical model of the phenomenon. It takes into account both the stress state and the water concentration in the walls of the shell at the onset of the instability. Moreover, it considers the invariance of the cavity volume at the onset of instability, which is due to the impossibility of instantaneously changing the cavity volume filled with water. Eventually, it is shown that the semi-analytic model matches very well the outcomes of the numerical experiments far from the initial regime; the ranges of validity of the approximated analytical model are also discussed.